STRATEGI PENGEMBANGAN EKONOMI KREATIF KABUPATEN WAJO - Nasriah Akil (Jurnal Bisnis dan Kewirausahaan, 2015)
The model used in the development of the creative economy in Wajo, is adopting a model of creative economic development nationwide, but the main actors used the concept of Quadruple Helix (Government, intellectuals, business and community) which is supported by the industry, technology, government, institutions, and financial mediation institutions. The main foundation of this model is a creative community. To support the creative economy development model in Wajo, that the government establish an Integrated Business Service Centre (Plut) and Regional Innovation Center (PID) to train undergraduate become consultants and managers.